Early announcement of international conference - Preventing emerging occupational and environmental risks in southern Asia and beyond, New Delhi, India, January 2009 - Kant Joshi, Tushar (European Journal of Oncology and Environmental Health, 2008)
The Employees State Insurance Corporation of India, one of the largest insurers in the world, are collaborating with the Centre for Occupational and Environmental Health, at Maulana Azad Medical College, New Delhi, the Collegium Ramazzini, the European Ramazzini Foundation, and Drexel University, School of Public Health to organize a state-of-the-art three day international conference on the above topic at New Delhi, India from 11 January through 14 January 2009...